Herramienta observacional para analizar la cobertura del ataque en voleibol - Hileno, R.; Busca, B. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2012)
This study presents a methodological proposal that uses a competitive model to analyze a game action in volleyball known as the attack coverage. An ad hoc observation tool was designed to carry out synchronic and diachronic analyses of the action under study whilst taking into account the different levels of behavioural interaction that can occur between players on the same team. Once the quality of the data had been verified, we carried out an exploratory study of the libero player and found 19 coverage patterns in different game situations. The results reinforced the idea that each player should take responsibility for a specific area of coverage in each particular attack zone.